ANALYSIS OF OVERPRESSURE CHARECTERISTICS IN X FIELD, JAMBI SUB-BASIN, SOUTH SUMATRA BASIN - Dimas Putra, Andry
X Field is a hydrocarbon-producing field located in the Jambi Sub-Basin, South Sumatra Basin, known for its overpressured zones. Pore pressure analysis is vital for supporting oil and gas development in this basin and mitigating drilling challenges such as kicks and blowouts caused by overpressure. This study aims to determine the distribution of top of overpressure, estimate pore pressure, identify mechanisms of overpressure generation, and analyze the relationship between the stratigraphy of the study area and the occurrence of overpressure. This research employs data from three wells (X-1, X-2, and X-3, including wireline logs, mud weight, pressure test data, temperature data, and drilling reports. The Eaton method was applied to estimate pore pressure. The results reveal that the top of overpressure in Wells X-1, X-2, and X-3 occurs at depths of 1910, 1930, and 1980 m, respectively, within the Gumai Formation. The estimated pore pressure gradient ranges from 0.441 to 0.840 psi/ft. Overpressure in all three wells is attributed to the loading mechanism, predominantly controlled by the sedimentation rate of the Gumai Formation, which mainly consists of clay.